AN ANALYSIS OF TURN-TAKING RULES IN A COMEDY FILM ENTITLED BRUCE ALMIGHTY - Qori Nuraeni, - (2012)
Conversation is an activity when one person communicates through speaking to another people. At least two persons are needed to do conversation. Speakers who are involved in the conversation have to concern who should speak and when the speakers start to speak. Consequently, there must be some principles which govern who gets to speak, namely, principles of turn-taking. The research focuses on the turn-taking rules in Bruce Almighty film. Since a film contains conversation among actors, it is possible to analyze the conversation in the film. The purpose of the research is to investigate the turn-taking rules that occur in conversation among actors and also some possible factors that influence the turn-taking behavior in Bruce Almighty film. The research uses descriptive analysis which is qualitative in nature. The main data is taken from the script which represents the conversation among actors in the film. The conversation among actors is then analyzed using the Organization of Turn-Taking for Conversation framework as proposed by Sacks, Schegloff, and Jefferson (1974). The research finds that there are 36 encounters, which is based on the scene, and it is found in Bruce Almighty film. From the 36 encounters, the Current Speaker Selects the Next Speaker (CS2TNS) rule, Self-Selection (SS) rule, and Current Speaker Continues (CSC) rule appear in almost all encounters in Bruce Almighty film. The most often rule which is applied in the film is Current Speaker Selects the Next Speaker (CS2TNS) rule. In addition, gender differences, personality differences, and power relation differences become some possible factors that influence the turn-taking behavior in conversation among actors in Bruce Almighty film. This result confirms the previous studies which were conducted by Wei-Dong (2007) and Hong-Mei (2008). Wei-Dong (2007) found that gender differences and personality differences can influence the turn-taking behavior in conversation. In addition, Hong-Mei (2008) adds another factor, that is, power relation differences which can influence the turn-taking behavior in conversation. The data might indicate that in every conversation there must be some rules, in this term turn-taking rules, which governs the organization of conversation. Moreover, the turn-taking behavior itself may vary for each speaker who is involved in conversation. It is possible that some factors such as gender differences, personality differences, and power relation between speakers' differences can affect the turn-taking behavior in conversation.